KEBIJAKAN CYBER ISLAMIC UNIVERSITY DALAM PENINGKATAN SDM DI ERA SOCIETY 5.0 - Fadli, Faisal; Miftah, Muhammad (Universitas Muhammadiyah Surakarta, 2023)
The Indonesian government, through the Ministry of Religion, has established the Islamic University cyber policy as one of the Ministry of Religion's 7 policy priorities. The cyber-Islamic university policy is motivated by the issue of equal distribution of education (especially Islamic education) in Indonesia which is still minimal. The Ministry of Religion records that there are tens of thousands of teacher educators who have not studied at university level. This then became one of the reasons for formulating a cyber-Islamic university policy with IAIN Nurjati as the first pilot project. In its implementation, CIU policy not only has a role in equalizing education in Indonesia, but also has a role in improving human resources in Indonesia. Human resources or HR is something that needs to be improved, in relation to the progress of the times until we reach the 5.0 era. In this research, the researcher aims to analyze the Islamic University cyber policy as one of the ways the government has taken to improve human resources and the role of this policy in preparing Indonesian society to adapt to the Society 5.0 era. The research method used by researchers is library research, using the Ministry of Religion Decree regarding the appointment of IAIN Nurjadi as a pilot project for implementing CIU policies as the main data source. Researchers use a theory related to society 5.0 which was initiated by Fukuda, the idea is that society 5.0 has a humanist side where humans are made the center so that society can experience a quality social atmosphere. The results of this research are that researchers found that human resources are an important thing to improve in the era of society 5.0, and one way to improve human resources in Indonesia is the implementation of the cyber-Islamic university policy